Association of multimorbidity patterns and order of physical frailty and cognitive impairment occurrence: a prospective cohort study. - Wang, Shuomin; Li, Qianyuan; Hu, Jianzhong; Chen, Qirong; Wang, Shanshan; Xue, Qian-Li; Huang, Chongmei; Sun, Hongyu; Liu, Minhui (Age & Ageing, 2025)
Background Chronic conditions often co-occur in specific disease patterns. Certain chronic diseases contribute to incident frailty or cognitive impairment (CI), but the associations of multimorbidity patterns and the order of frailty and CI occurrence remain unclear. Objectives To determine multimorbidity patterns amongst older adults and their associations with the order of frailty and CI occurrence. Design Prospective cohort study. Methods Using data from National Health and Aging Trends Study, 7522 community-dwelling participants were included and followed up for four years. Latent class analysis was conducted to identify multimorbidity patterns with clinical meaningfulness. Fine and Grey competing risks models were used to examine the associations between multimorbidity patterns and different orders of frailty and CI occurrence (frailty-first, CI-first, frailty-CI co-occurrence). Results Four multimorbidity patterns were identified: cardiometabolic, osteoarticular, cancer-dominated and psychiatric/multisystem pattern. Compared to non-multimorbidity, all four multimorbidity patterns were associated with a higher risk of developing frailty-first, but not developing CI-first. Specifically, the psychiatric/multisystem pattern had the highest risk of developing frailty-first ( Sub-distribution hazard ratios [SHR] = 3.74, 95% confidence intervals = 2.96, 4.71), followed by osteoarticular pattern (SHR = 2.53, 95% CI = 1.98, 3.22) and cardiometabolic pattern (SHR =2.41, 95% confidence intervals = 1.96, 2.98). In addition, only participants from psychiatric/multisystem and cardiometabolic pattern showed a higher risk of frailty-CI co-occurrence. Conclusions Our findings highlight the etiological heterogeneity between physical frailty and CI. Clinician should be aware of multimorbidity clusters and thus provide more effective strategies for comorbid older adults to prevent the onset of these two geriatric syndromes.